AL-HUKM DAN AL-HAKIM: PRINSIP UTAMA DALAM SYARIAT ISLAM : Pengertian Hukum (al-hukm), Pembagian Hukum (al-hukm), Pengertian Pembuat Hukum (al-hakim) - Ahmad In'am Awaluddin (Penerbit Hellow Pustaka, 2025)
This study discusses al-hukm and al-hakim as the main principles in Islamic law. Law is a text or texts contained in the Qur'an and Hadith that regulate the guidelines for human life, which are texts or decrees originating from Allah SWT and His Messenger relating to the deeds of mukallaf, whether in the form of commands, prohibitions, or recommendations to do or refrain from doing something. Law or al-hukm is divided into two types, namely, first, taklifi law, which is the word of Allah SWT (the book of Allah) relating to all the deeds of mukallaf, both in terms of iqtidha' and takhyir. Second, wadh'i law is a command from Allah in the form of provisions established by Allah, which do not directly regulate the actions of mukallaf, but are also related to the actions of mukallaf. Then, in addition to that, there is also al-hakim or judge, which in fiqh terminology is also used for people who have decided on the law in court. Meanwhile, in the study of usul fiqh, the judge is the determiner and also the maker of sharia law in its true sense. Ulema usul fiqh agree that the real judge who is the true maker of sharia law is Allah SWT. Keywords: Law, Judge, Islamic Sharia.